2020
DOI: 10.1038/s41419-020-2459-3
|View full text |Cite|
|
Sign up to set email alerts
|

Cold atmospheric plasma induces GSDME-dependent pyroptotic signaling pathway via ROS generation in tumor cells

Abstract: Cold atmospheric plasma (CAP) has been proposed as a novel promising anti-cancer treatment modality. Apoptosis and necrosis have been revealed in CAP-induced cell death, but whether CAP induces pyroptosis, another kind of programmed cell death is still unknown. In the present study, we first reported that CAP effectively induced pyroptosis in a dose-dependent manner in Gasdermin E (GSDME) high-expressed tumor cell lines. Interestingly, the basal level of GSDME protein was positively correlated with the sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 46 publications
2
55
0
1
Order By: Relevance
“…Local treatment with H-FIRE not only ablates the primary tumor, but also reduces metastatic lesions, which is dependent on the adaptive immune system [ 130 ]. Recently, Xiaorui et al reported that cold atmospheric plasma, a novel promising anti-cancer treatment, induces GSDME-dependent pyroptotic cell death in GSDME-expressing tumor cells [ 131 ].…”
Section: Main Textmentioning
confidence: 99%
“…Local treatment with H-FIRE not only ablates the primary tumor, but also reduces metastatic lesions, which is dependent on the adaptive immune system [ 130 ]. Recently, Xiaorui et al reported that cold atmospheric plasma, a novel promising anti-cancer treatment, induces GSDME-dependent pyroptotic cell death in GSDME-expressing tumor cells [ 131 ].…”
Section: Main Textmentioning
confidence: 99%
“…In contrast to apoptosis-cell death without any inflammatory outcome-cell death mechanisms that inherently result in inflammation are pyroptosis and immunogenic cell death (ICD). Recently, CAP was shown to induce pyroptosis, another highly inflammatory programmed cell death, via ROS generation in gasdermin E expressing tumour cell lines [114]. The basal level of gasdermin E protein positively correlates with the cell's sensitivity to CAP-induced pyroptosis, which depends on the activation of mitochondrial pathways (JNK/cytochrome c/caspase-9/caspase-3) and the cleavage of gasdermin E [114].…”
Section: Immune Response Activating Cell Deathmentioning
confidence: 99%
“…Recently, CAP was shown to induce pyroptosis, another highly inflammatory programmed cell death, via ROS generation in gasdermin E expressing tumour cell lines [114]. The basal level of gasdermin E protein positively correlates with the cell's sensitivity to CAP-induced pyroptosis, which depends on the activation of mitochondrial pathways (JNK/cytochrome c/caspase-9/caspase-3) and the cleavage of gasdermin E [114]. ICD, on the other hand, involves changes in the composition of the cell surface, as well as the release of soluble mediators, which operate on a series of receptors expressed by dendritic cells, to stimulate the presentation of tumour antigens to T cells and elicit tumour cell death [115].…”
Section: Immune Response Activating Cell Deathmentioning
confidence: 99%
“…Так, перекись водорода и свободные радикалы вызывают снижение митохондриального мембранного потенциала, высвобождение апоптоз-индуцирующего фактора в цитозоль, снижают экспрессию антиапоптотических белков в митохондриях [59,67]. Повреждение митохондрий может быть ответственно и за развитие пироптоза за счет механизмов, утилизирующих высвобождение цитохрома с, активацию каспазы-9 и каспазы-3 [68]. Кроме того, аккумуляция активных форм кислорода в митохондриях, вызванная действием бесклеточной питательной среды, обработан-ной ХП, предшествует развитию аутофагии и митофагии в клетках [59].…”
Section: влияние хп на метаболизм клетокunclassified